THE ELABORATION OF THE OPTIMAL SYNTHESIS ALGORITHM FOR COMPLEX PROCESSING INFORMATION OF THE SPATIAL POSITION OF THE UPPER-AIR RADIOSONDE - E. A. Bolelov; Yu. M. Ermoshenko (Научный вестник МГТУ ГА, 2016)
The article considers the elaboration of the problem of optimal algorithm synthesis of complex signal processing of satellite GLONASS/GPS systems navigation relayed from the Board of the upper-air radiosonde and the output data upper-air radar to determine the spatial coordinates of upper-air radiosonde. The upper-air sounding is performed with the help of technical means of radio sounding system of atmosphere, including the upper-air radiosonde, manufactured in free flight, and ground supporting equipment, which includes devices for signal processing of upper-air radiosonde and preparation of the operational upper-air messages. The peculiarity of atmosphere radio sounding of domestic system is the measurement with method of radar slant range to upper-air radiosonde, the viewing angles of the antenna upper-air radar to determine azimuth and elevation of upper-air radiosonde. The disadvantage of the radar method of radiosonde support is the relatively low accuracy of determining the coordinates of the radiosonde and the possible disruption of automatic tracking in angular coordinates. Satellite navigation system based on the microwave sensors has clear advantages in terms of efficiency, size, mobility, and use on mobile objects, however, with significant drawbacks associated primarily with the geometric factor and the error propagation of the navigation signal. The article presents a mathematical model useful incoherent GLONASS/GPS signals, relayed by the upper-air radiosonde, and interference on the input receiver ground point for complex information processing, and mathematical models of output data in upper-air radars.